REMAJA dan KRIMINALITAS (Studi di lembaga permasyarakatan klas II B Anak Dikota Pekanbaru) - Hadi, Alpin; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study analyzes the juvenile criminal acts committed in the city of Pekanbaru. Is a social phenomenon that occurs in urban communities, Cities are centers of crime or criminality, it is because in urban areas there is intense competition often even unhealthy. Crime in line with the expanding urban population increases, development, modernization and urbanization. Teenagers are one of the victims who are especially susceptible to committing a crime because sometimes they can be entangled in the one thing that is often tempting for them to try and gradually becomes a pleasure and continue to do. Juvenile delinquency in the study of social problems can be categorized into deviant behavior. In the perspective of deviant behavior occurs because there is a social problem of deviant behavior of various social rules or of values and social norms that apply. The data analysis was done by qualitative deskrpitif, data collection techniques in this research is purposive where the number of respondents totaled 6 people who have been in prison Class II B Children Pekanbaru. From the research field that the causes of juvenile crimes is Broken Home, Poverty, waning benchmark values and norms and mimic peers.Keywords: Teenagers, Crime, Behavior